Competition in Retail Banking Services in Latin America - World Bank (World Bank, Washington, DC, 2020)
This paper analyzes competition in the retail banking markets in Latin America. Retail banking services, that is banking products and services for consumers and small businesses, including deposit accounts and related services such as ATMs, direct debit and credit transfers, and credit lines, are an increasingly important segment of the banking business in the region. Yet the provision of banking services in Latin America remains very expensive by international comparison. While many factors contribute to high costs of financial intermediation in the region, restricted or distorted competition may be an important supply-side driver. Based on a survey with competition authorities and financial regulators in seven large Latin American economies (LA-7) combined with publicly available data and information, this paper attempts to shed light on entry and contestability in retail banking services in the region, including access to the financial infrastructure, payments systems and credit reporting systems (CRSs), while discussing the status of competition law enforcement and advocacy initiatives. Given limited antitrust enforcement and advocacy initiatives in the field of retail banking in LA-7, the objective of the paper is to advance knowledge on the status of competition in the retail banking segment while stimulating further country-product specific analysis.